The Effect of Education on Self-Care Management in Hypertensive Elderly in the Bandung Health Center Area, Bandung District, Tulungagung Regency - Yulia Nurfatna; Novita Ana Anggraini (Journal of Health Science Community, 2023)
The elderly are an economically unstable population when compared to those who are young, and it turns out that the more vulnerable are the elderly. Hypertension is a non-communicable disease, and this degenerative disease is widespread, has a very high mortality rate and affects the quality of life and productivity of a person. Self-care management is the ability of a person to participate in self-esteem activities to save one's life, improve, maintain one's health and well-being.The design of this study uses an experimental design with a pre-experimental approach. This study was conducted on 39 respondents using the simple random sampling method which was conducted in May 2022. Statistical test results using the wilcoxon test to analyze the effect of education on self-care management in hypertensive elderly obtained a significant value of ρ value (0.003) with α (0.05) because ρ < α there is an educational influence on self-care management in hypertensive elderly. Based on the results of this study shows the influence of education on self-care management in hypertensive elderly, and this education can be an effort by the elderly to find out and prevent hypertension with self-care management in hypertensive elderly.